2017
DOI: 10.3174/ajnr.a5441
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Characteristics Associate with Tumor-Associated Macrophages in Glioblastoma and Provide an Improved Signature for Survival Prognostication

Abstract: BACKGROUND AND PURPOSE:In glioblastoma, tumor-associated macrophages have tumor-promoting properties. This study determined whether routine MR imaging features could predict molecular subtypes of glioblastoma that differ in the content of tumorassociated macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 39 publications
2
37
1
1
Order By: Relevance
“…Caponegro et al also described a correlation between the presence of TAMs and a poorest prognosis in GB (Caponegro et al, 2018). Furthermore, a study based on magnetic resonance imaging in GB showed that highly aggressive tumors were also correlated with the presence of TAMs (Zhou et al, 2018). Taking into account these findings, the presence of TAMs in GB has been well proven.…”
Section: The Presence Of Tams In Gb: Reality or Not?mentioning
confidence: 90%
“…Caponegro et al also described a correlation between the presence of TAMs and a poorest prognosis in GB (Caponegro et al, 2018). Furthermore, a study based on magnetic resonance imaging in GB showed that highly aggressive tumors were also correlated with the presence of TAMs (Zhou et al, 2018). Taking into account these findings, the presence of TAMs in GB has been well proven.…”
Section: The Presence Of Tams In Gb: Reality or Not?mentioning
confidence: 90%
“…In osteosarcomas, there is no difference in the clinical outcome [35]. However, ALT is associated with a better patient outcome in glioblastoma [36]. Differential prognosis of ALT may rely on the different genetic and epigenetic events responsible for TMMs.…”
Section: Telomere Maintenance By Telomerase or Altmentioning
confidence: 99%
“…The tumor-associated imaging abnormality on our patients' pre-surgical MR images were segmented by trained individuals. From these segmentations, we calculate the volume of the imaging abnormality (mm 3 ). Every patient in this cohort has a "T1Gd volume", quantifying the size of the imaging abnormality on the presurgical T1Gd image that was closest to the date of surgery.…”
Section: Biomedical Imagingmentioning
confidence: 99%
“…Cystic fluid is typically isointense with cerebrospinal fluid (CSF) on T2 and FLAIR MRI and has a notably smooth texture. While these cysts are more common in lower grade gliomas (e.g., juvenile pilocytic astrocytoma, ganglioglioma) and non-glioma tumors with good prognosis (e.g., hemangioblastoma), between 7-23% of GBM tumors can also present with a dominant central cyst (rather than central necrosis) ( Figure 1B) [2,3]. We will refer to these as cystic GBMs and those without a significant cystic component as noncystic GBMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation